Development Of Alliance Strategy in The Implementation Of Risk-Based EPC Projects To Enhance Cost Performance Capacity Of PT XYZ - Azhari Wicaksono, Andri; Isvara, Wisnu (Journal Research of Social Science, Economics, and Management, 2024)
In Indonesia’s construction industry, EPC (Engineering, Procurement, Construction) contracts have become a widely recognized option, especially for projects with high levels of complexity. PT XYZ, as a state-owned construction company (BUMN), is actively involved in EPC projects in sectors such as power plants, factories, and oil processing. Given the high complexity of these projects, PT XYZ needs to form a consortium with partners to complement its limited capabilities. However, the formation of a consortium introduces risks that could potentially harm PT XYZ during project execution. This research aims to develop a risk management strategy to assist PT XYZ in making the right decisions in managing consortium risks, thereby enhancing the company’s capacity to complete EPC projects. The research findings reveal that the highest risks occur during the construction phase, categorized as “Medium to High” level. These risks include "The Vendor Chosen by the Partner Lacks Competence", "Redesign Work, Design Errors or Defects, and Poor Design Variation Process Management", and "Poor Coordination Process Between Design, Procurement, and Construction"